Beethoven Last 10 Quartets and the Grand Fugue, London String Quartet, November 3 and 4, 1934 (Wolfsohn Musical Bureau of New York; New York, 2020)
Program for series of Beethoven middle period and late string quartets by the London String Quartet, Nov. 3-4, 1934, Town Hall, New York.